Functional integration changes in regional brain glucose metabolism from childhood to adulthood - Trotta, Nicola; Archambaud, Frédérique; Goldman, Serge; Baete, Kristof; Van Laere, Koen; Wens, Vincent; Van Bogaert, Patrick; Chiron, Catherine; De Tiège, Xavier (Human brain mapping, 2016)
The aim of this study was to investigate the age‐related changes in resting‐state neurometabolic connectivity from childhood to adulthood (6–50 years old). Fifty‐four healthy adult subjects and twenty‐three pseudo‐healthy children underwent [18F]‐fluorodeoxyglucose positron emission tomography at rest. Using statistical parametric mapping (SPM8), age and age squared were first used as covariate of interest to identify linear and non‐linear age effects on the regional distribution of glucose metabolism throughout the brain. Then, by selecting voxels of interest (VOI) within the regions showing significant age‐related metabolic changes, a psychophysiological interaction (PPI) analysis was used to search for age‐induced changes in the contribution of VOIs to the metabolic activity in other brain areas. Significant linear or non‐linear age‐related changes in regional glucose metabolism were found in prefrontal cortices (DMPFC/ACC), cerebellar lobules, and thalamo‐hippocampal areas bilaterally. Decreases were found in the contribution of thalamic, hippocampal, and cerebellar regions to DMPFC/ACC metabolic activity as well as in the contribution of hippocampi to preSMA and right IFG metabolic activities. Increases were found in the contribution of the right hippocampus to insular cortex and of the cerebellar lobule IX to superior parietal cortex metabolic activities. This study evidences significant linear or non‐linear age‐related changes in regional glucose metabolism of mesial prefrontal, thalamic, mesiotemporal, and cerebellar areas, associated with significant modifications in neurometabolic connectivity involving fronto‐thalamic, fronto‐hippocampal, and fronto‐cerebellar networks. These changes in functional brain integration likely represent a metabolic correlate of age‐dependent effects on sensory, motor, and high‐level cognitive functional networks. Hum Brain Mapp 37:3017–3030, 2016. © 2016 Wiley Periodicals, Inc.